Depression, Self-Care, and Medication Adherence in Type 2 Diabetes: Relationships across the full range of symptom severity - Gonzalez, Jeffrey S. (Diabetes Care, 2007)
OBJECTIVE: We examined the association between depression, measured as either a continuous symptom severity score or a clinical disorder variable, with self-care behaviors in type 2 diabetes. RESEARCH DESIGN AND METHODS: We surveyed 879 type 2 diabetic patients from two primary care clinics using the Harvard Department of Psychiatry/National Depression Screening Day Scale (HANDS), the Summary of Diabetes Self-Care Activities, and self-reported medication adherence. RESULTS: Of the patients, 19% met the criteria for probable major depression (HANDS score ≥9), and an additional 66.5% reported at least some depressive symptoms. After controlling for covariates, patients with probable major depression reported significantly fewer days' adherent to diet, exercise, and glucose self-monitoring regimens (P < 0.01) and 2.3-fold increased odds of missing medication doses in the previous week (95% CI 1.5–3.6, P < 0.001) compared with all other respondents. Continuous depressive symptom severity scores were better predictors of nonadherence to diet, exercise, and medications than categorically defined probable major depression. Major depression was a better predictor of glucose monitoring. Among the two-thirds of patients not meeting the criteria for major depression (HANDS score <9, n = 709), increasing HANDS scores were incrementally associated with poorer self-care behaviors (P < 0.01). CONCLUSIONS: These findings challenge the conceptualization of depression as a categorical risk factor for nonadherence and suggest that even low levels of depressive symptomatology are associated with nonadherence to important aspects of diabetes self-care. Interventions aimed at alleviating depressive symptoms, which are quite common, could result in significant improvements in diabetes self-care.